2006
DOI: 10.1016/j.ejheart.2005.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic value of urine NT‐proBNP levels in heart failure patients

Abstract: Background: Plasma NT-proBNP levels are sensitive markers of ventricular dysfunction. However, studies of natriuretic peptides in urine are limited. Aims: To compare urine and plasma NT-proBNP levels and to investigate the diagnostic and prognostic value of urine levels in heart failure (HF). Methods: Urinary and plasma NT-proBNP levels were measured in 96 HF patients and 20 control subjects. The patients were functionally classified according to the NYHA criteria. Results: Urine NT-proBNP was higher in HF pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
40
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 36 publications
5
40
1
Order By: Relevance
“…Our data indicate that immunoreactive NT-proBNP is present in human urine as multiple fragments of the 76 -amino acid peptide. We confirmed previous work showing that urine NT-proBNP immunoreactivity correlates with concurrent plasma concentrations (11,12,16 ) in patients with heart failure, is significantly increased in patients with heart failure compared with healthy controls (11,12,15,16 ), and correlates inversely with left ventricular ejection fraction (13 ) and creatinine clearance (12 ).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Our data indicate that immunoreactive NT-proBNP is present in human urine as multiple fragments of the 76 -amino acid peptide. We confirmed previous work showing that urine NT-proBNP immunoreactivity correlates with concurrent plasma concentrations (11,12,16 ) in patients with heart failure, is significantly increased in patients with heart failure compared with healthy controls (11,12,15,16 ), and correlates inversely with left ventricular ejection fraction (13 ) and creatinine clearance (12 ).…”
Section: Discussionsupporting
confidence: 78%
“…Analysis of patients with documented heart failure and healthy controls confirmed that urine NT-proBNP concentrations are increased in heart failure (11,12,15,16 ). The inverse relationship between urine NT-proBNP and left ventricular ejection fraction, together with correlations between plasma and urine concentrations in heart failure, suggests that urine NT-proBNP immunoreactivity is a potential biomarker in heart failure, as previously suggested (11)(12)(13)(14)(15)(16)(17).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Renal clearance of NT-proBNP is also supported by the extremely high concentrations of NTproBNP in hemodialysis patients (8 ), although this finding may be explained, in part, by accompanying cardiovascular disease (9 ). Renal clearance is further supported by the fact that NT-proBNP can be detected in urine (10 ), although the possibility that some local production occurs within the kidneys cannot be entirely excluded (11 ).…”
mentioning
confidence: 98%